P065 Regulation of joint destruction by activin a in rheumatoid arthritis. (March 2019) - Kracke, V; Fennen, M; Intemann, J; Werbenko, E; de Gorter, D; Paruzel, P; Pap, T; Dankbar, B
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Activins and inhibins belong to the transforming growth factor β family. Activins are disulphide-linked homo- or heterodimers consisting of two inhibin β chains (βA, βB) that are expressed in many cell types. However, activin A (βA βA) is the only activin that is expressed in bone and cartilage. Moreover, activin A has been demonstrated not only to stimulate receptor activator of NF-κB ligand (RANKL)-induced osteoclast (OC) differentiation but also to inhibit osteoblast differentiation. Objectives: Here we investigate the impact of activin A on joint destruction in rheumatoid arthritis. Methods: Synovial tissue samples from rheumatoid arthritis (RA) and osteoarthritis (OA) patients were analysed by immunohistochemical staining. For in vitro experiments, synovial fibroblasts (FLS) were isolated from hind paws of WT mice. Effects of cytokines on the secretion of activin A by mouse FLS were evaluated by ELISA. Bone marrow-derived macrophages (BMM) were isolated from femurs and tibias of WT mice and differentiated into osteoclasts in the presence of macrophage colony-stimulating factor (M-CSF) and RANKL with or without activin A. OC differentiation was characterised by TRAP staining. Resorption activity was determined by quantification of osteoclast-mediated pit formation on a calcium phosphate-coated plate. Furthermore, osteoclast-specific gene expression as well as the activation of SMAD2 in BMMs, OCs and FLS were analysed by immunoblotting. The interaction of phospho-SMAD2 with NFATc1 was evaluated by co-immunoprecipitation using Dynabeads. Results: We demonstrate that activin A is highly abundant in the synovium of RA but not of OA patients. In vitro, activin A secretion by FLS was strongly enhanced by pro-inflammatory cytokines. Furthermore, activin A strongly enhanced the RANKL-mediated differentiation of BMMs into mature OCs, reflected by a significantly increased OC number and OC size. Moreover, concomitant administration of activin A led to a significant increase of the total resorption area as well as resorption area per pit, indicating an increased activity of individual OCs. Furthermore, activin A enhanced the RANKL-induced expression OC differentiation markers, but alone was not able to induce OC differentiation. Analyses of signaling pathways revealed that activin A induce the activation of SMAD2 in BMMs and OCs. Finally, upon co-stimulation with RANKL, activin A resulted in an increased interaction between activated SMAD2 and NFATc1. Conclusions: The data strongly suggest that increased expression of activin A in the arthritic joint is associated with enhanced osteoclast formation, promoting joint destruction in rheumatoid arthritis. Disclosure of Interest: None declared.